Demokrati som transgression: Civilsamfundsalternativer i indvandringspolitik - Jørgensen, Martin Bak; Agustín, Óscar García (Academic Quarter | Akademisk kvarter, 2011)
The same kind of inclusive understanding is developed in the article Demokrati som transgression by Martin Bak Jørgensen & Óscar García Agustín who argue from Jacques Ranciere’s position that democracy is only achievable when those who are usually excluded are included. Focussing specifically on Denmark’s immigration policies and how these are challenged by transgressive groups which attempt to resist neo-liberal discursive closure of the public sphere.